The Management Information System User: An Exploratory Behavioral Analysis - Schewe, Charles D. (Academy of Management Journal, 1976)
A behavioral study utilizing an attitudinal model explored the relationships between management information system users' perceptions of their computer system, perceived variables exogenous to the system, attitudes, and system usage. The major finding indicated no significant relationship between attitudes and system usage behavior.